Zero-crossing intervals of Gaussian and symmetric stable processes - Cao, Yufei (2017)
The zero-crossing problem is the determination of the probability density function of the intervals between the successive axis crossings of a stochastic process. This thesis studies the properties of the zero-crossings of stationary processes belonging to the symmetric-stable class of Gaussian and non-Gaussian type, corresponding to the stability index nu=2 and 0<nu<2 respectively.